The determinants of local employees intention to use islamic home financing / Zakwan Ahmad and Mohammad Hilal Nawawi - Ahmad, Zakwan; Nawawi, Mohammad Hilal (2014)
This research paper title is “Determinant of local employees’ Intention to Use Islamic Home Financing. The researcher intended to identify the factors that influence the respondents’ intention to use Islamic home financing either current or future use. Therefore the researcher has proposed four independent variables that might influence the respondents intention namely social influence, knowledge, marketing and shari’ah compliance. Further detailed of the variables is discussed in Chapter 2. On Chapter 1 of the report, the researcher includes information regarding the background of the study, the objective of the study and etc. The population for this research in the area of Seberang Perai Tengah and the researcher decided to take 150 of the employees as the research sample, further detailed on the research methodology was discuss in Chapter 3. In order to achieve the research objective, the researcher had conduct five analysis which are frequency analysis, descriptive analysis, reliability analysis, hypothesis testing (correlation analysis) and multiple regression. The entire analysis finding is present in Chapter 4. The last chapter which is Chapter 5 discuss regarding conclusion and recommendations from the researcher